Eudebeiolide B Inhibits Osteoclastogenesis and Prevents Ovariectomy-Induced Bone Loss by Regulating RANKL-Induced NF-κB, c-Fos and Calcium Signaling - Mi-Hwa Kim; Hyung-Jin Lim; Seon Gyeong Bak; Eun-Jae Park; Hyun-Jae Jang; Seung Woong Lee; Soyoung Lee; Kang Min Lee; Sun Hee Cheong; Seung-Jae Lee; Mun-Chual Rho (MDPI AG, 2020)
Eudebeiolide B is a eudesmane-type sesquiterpenoid compound isolated from Salvia plebeia R. Br., and little is known about its biological activity. In this study, we investigated the effects of eudebeiolide B on osteoblast differentiation, receptor activator nuclear factor-κB ligand (RANKL)-induced osteoclastogenesis in vitro and ovariectomy-induced bone loss in vivo. Eudebeiolide B induced the expression of alkaline phosphatase (ALP) and calcium accumulation during MC3T3-E1 osteoblast differentiation. In mouse bone marrow macrophages (BMMs), eudebeiolide B suppressed RANKL-induced osteoclast differentiation of BMMs and bone resorption. Eudebeiolide B downregulated the expression of nuclear factor of activated T-cells 1 (NFATc1) and c-fos, transcription factors induced by RANKL. Moreover, eudebeiolide B attenuated the RANKL-induced expression of osteoclastogenesis-related genes, including cathepsin K (Ctsk), matrix metalloproteinase 9 (MMP9) and dendrocyte expressed seven transmembrane protein (DC-STAMP). Regarding the molecular mechanism, eudebeiolide B inhibited the phosphorylation of Akt and NF-κB p65. In addition, it downregulated the expression of cAMP response element-binding protein (CREB), Bruton's tyrosine kinase (Btk) and phospholipase Cγ2 (PLCγ2) in RANKL-induced calcium signaling. In an ovariectomized (OVX) mouse model, intragastric injection of eudebeiolide B prevented OVX-induced bone loss, as shown by bone mineral density and contents, microarchitecture parameters and serum levels of bone turnover markers. Eudebeiolide B not only promoted osteoblast differentiation but inhibited RANKL-induced osteoclastogenesis through calcium signaling and prevented OVX-induced bone loss. Therefore, eudebeiolide B may be a new therapeutic agent for osteoclast-related diseases, including osteoporosis, rheumatoid arthritis and periodontitis.